Essentials for developing cultural competence in occupational therapy: the cultural competence workshop for occupational therapy practitioners (CCWOT) - Song, Jin (2019)
Cultural competence refers to healthcare professionals’ ability to self-reflect on their own values and beliefs, how these values and beliefs impact their professional behaviors, and the ability to address cultural needs of their clients. Evidence demonstrated the positive relation between the culturally competent care and clients’ satisfaction, trust in provider, treatment adherence and therapeutic alliance. Although the occupational therapy (OT) profession calls for client- and culturally-centered practice, OT practitioners are not always confident in their abilities to address cultural needs of their clients in their daily practices. This project aims to enhance OT practitioners’ cultural competence and confidence in working with diverse clients in hospitals. The first step of this project was to develop an explanatory model of the complexities in practicing culturally competent care. Inspired by the Process of Cultural Competence in the Delivery of Healthcare Services (2010) (Transcultural C.A.R.E. Associates, 2015) and Schein’s Organizational Culture Model (1996), the model exemplifies that culturally competent care is about interactions between clients and therapists’ traits that are not easily observable. Many barriers may limit the delivery of culturally competent care. However, cultural encounters offer valuable learning experiences by which providers can enhance their cultural awareness, knowledge, skill, and desire to provide higher quality of individualized care. Evidence to support the constructs of this model and the interactions among them is presented. The second step included a literature review of evidence on previous research of effective interventions used to enhance cultural competence. The essential elements of successful programs were synthesized to develop the Cultural Competence Workshop for Occupational Therapy Practitioners (CCWOT). The proposed program included (1) knowledge on cultural behaviors, values, and assumptions, (2) reflective practice, and (3) opportunities for experiential learning to foster knowledge and reflection by engaging in cultural encounters A mix-methods research design to examine the program’s effectiveness, a funding plan with available local resources, budget, and potential funding sources, and dissemination activities targeting OT practitioners, therapy directors and clients are also presented. This project provides OT practitioners an opportunity to establish respectful, collaborative and effective therapeutic alliances between practitioners and clients of all cultures. The ultimate goal is to assist our clients to live life to its fullest within their own cultures.